2016
DOI: 10.1007/s00162-016-0382-0
|View full text |Cite|
|
Sign up to set email alerts
|

Theoretical treatment of fluid flow for accelerating bodies

Abstract: Most computational fluid dynamics simulations are, at present, performed in a body-fixed frame, for aeronautical purposes. With the advent of sharp manoeuvre, which may lead to transient effects originating in the acceleration of the centre of mass, there is a need to have a consistent formulation of the Navier–Stokes equations in an arbitrarily moving frame. These expressions should be in a form that allows terms to be transformed between non-inertial and inertial frames and includes gravity, viscous terms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…This appears as a source term on the right hand side of the momentum equation for the particle phase [65]. It is assumed that the air phase is unaffected by centrifugal forces due to its relatively low density.…”
Section: Test Case Descriptionmentioning
confidence: 99%
“…This appears as a source term on the right hand side of the momentum equation for the particle phase [65]. It is assumed that the air phase is unaffected by centrifugal forces due to its relatively low density.…”
Section: Test Case Descriptionmentioning
confidence: 99%
“…This appears as a source term on the right hand side of the momentum equation for the particle phase [62]. It is assumed that the air phase is unaffected by centrifugal forces due to its relatively low density.…”
Section: Test Case Descriptionmentioning
confidence: 99%
“…Acceleration and deceleration are often encountered in a multitude of engineering applications including, helicopter rotors in hover and forward flight [1], missile aerodynamics [2], manoeuvring fighter planes during acceleration and deceleration [3], aerodynamics around a decelerating Formula 1 and various high performance cars [4] and aero-ballistic ordinance [5]. Accelerating/decelerating motion is considered here to combine unsteady translation and unsteady rotation of an object immersed in a compressible fluid [2,3,6,7,8,9]. This can also include combined oscillating translation and rotation [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the above studies, the effects observed increased with an increase in the acceleration magnitude. Thus in applications where the acceleration/deceleration is significant, it becomes important to not only investigate the transient effects but also the acceleration effects that result from the acceleration of the objects centre of mass [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation